Designing Prototype of Acoustic & Resistivity Transducer - Muhammad Ashraf bin Mohd Fahari, Muhammad Ashraf (Universiti Teknologi Petronas, 2012)
A seismic wave is acoustic energy transmitted by vibration of rock particles. Low energy waves are approximately elastic, leaving the rock mass unchanged by their passage, but close to a seismic source the rock may be shattered and permanently distorted. Reservoir characterization and monitoring using seismic technology has seen tremendous progress and recognition in recent years. In theory, time-lapse seismology measures the spatial and temporal changes related to reservoir changes and processes and it provide data on whether these changes are large enough to resolve seismically. Other than seismic method, resistivity is one of alternative for geophysicist to characterize and monitoring the reservoir. Seismic and resistivity test normally done in different stages which create errors. This method affect the feasibility during test or experiment thus resulting in wrong interpretation for reservoir characteristic especially while monitoring water flooding. A device is being designed which has the capability to run seismic and resistivity monitoring on reservoir characterization at one time and feasibility will be the focus objective for this research by implementing several experiment with the new device designed. As a result of completing the research project, it expected for author to learn as much possible about geophysics application and able to apply while monitoring the devices. The author will focus on the application of seismic and resistivity test during water flooding monitoring. As the conclusion, implication of findings will be the feasibility of device by applying two geophysics principals which are seismic and resistivity during water flooding monitoring.